Wrapping tape operation for poststenotic aneurysm of ascending aorta during correction of aortic stenoses - Popov, V.; Bolshak, O.; Spysarenko, S. P.; Malysheva, T. A.; Lazorishinetz, V. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Purpose – to determine possibilities of correction of poststenotic aneurysm of ascending aorta (PAAA) by WTO. During 2005–2017 yy 174 patients (pts) with aortic stenoses (AS) and PAAA were operated in Institute. The following operation was performed: aortic valve replacement (AVR) + wrapping tape operaton (WTO) of AA. In all cases after AVR nylon tape (diamener 1 cm) was wrapping of AA by 5–9 tours and fixation between them and in proximal and distal part of AA. Hospital mortality was 0,6%. Echo examination of diameter of AA (mm): preoperative 47,5±1,6, postoperative 39,4±1,3, remote period 40,2±1,8. On the basis of clinical experience we recommend the expedient method of WTO for PAAA (diameter of AA till 5,5 cm) during AVR without prostheses of AA.